Laxative and antimicrobial activity of Senna spectabilis (Caesalpiniaceae) - Ospino, Luis; Negrón, Eudubertt; Salas, Rodolfo (Boletín del Centro de Investigaciones Biológicas, 1970)
Inhabitants that practice folk medicine in the Andean Region of Venezuela use preparations of Senna spectabilís (Caesalpiniaceae) for several remedies including natural laxatives, but biological activity of this botanical species is still undocumented. We characterized foliar material from Senna spectabilis (var. spectabilis) chemically and biologically. Crude extracts from leaves were prepared using organic solvents with increasing polarity, and assayed in-vivo for laxative activity on albino, Balbc mice. Additionally, presence of in-vitro antimicrobial activity was established against bacterial strains of Escherichia coli, Staphylococus aureus and Bacillus sp. Ethyl acetate (water soluble form) and methanol extracts showed moderate laxative activity. We characterized compounds isolated from ether extracts as carboxyl acids and compounds from methanol extracts as anthraquinones. Antibacterial activity of Senna spectabilis extracts (except ether and benzene) on Bacillus sp. colony growth is comparable to that of commercial discs, and indicates an interesting antimicrobial potential against other sporogenous strains of clinical and industrial importance.